Diagnosis of Ischemic Stroke with Manifestations of Status Epilepticus in Male Adolescents: A Case Report - Suherman, Rivana Sabania; Nugraha, Bunyamin (Jurnal Indonesia Sosial Sains, 2026)
Background: Stroke in children and adolescents, though rare, presents significant diagnostic challenges due to its atypical manifestations compared to adults. Ischemic stroke in this population can initially present with seizures, including status epilepticus, potentially delaying accurate diagnosis and appropriate management. Objective: This case report aims to describe the clinical presentation, diagnostic process, and management of an adolescent male with acute ischemic stroke whose primary manifestation was status epilepticus, highlighting the importance of considering stroke in the differential diagnosis of new-onset seizures. Methods: We report the case of a 14-year-old boy who presented to the emergency department with unconsciousness following prolonged seizures. Clinical history, physical examination, laboratory findings, and neuroimaging results were collected and analyzed. A non-contrast head CT scan was performed to investigate the underlying etiology. Results: The patient experienced recurrent seizures, including a prolonged episode lasting over one hour, which constituted status epilepticus. Initial vital signs and routine laboratory tests were unremarkable. A non-contrast CT scan revealed multiple ischemic lesions in the left internal capsule, left thalamus, left corona radiata, and subcortical regions of the left temporoparietal lobe, as well as the white matter of the right parietal lobe, with mass effect compressing the left lateral ventricle. These findings confirmed the diagnosis of acute ischemic stroke. The patient received supportive care, anti-seizure medication, and antiplatelet therapy, leading to gradual clinical improvement. Conclusion: This case underscores that ischemic stroke can present with status epilepticus in adolescents, a demographic where stroke is often not the initial consideration.